STUDENT CREATIVITY IN STEAM LEARNING THROUGH A POP-UP BOOK PROJECT BASED ON THE ENGINEERING DESIGN PROCESS - Ankai Wahyuni Tanjung Handayani; Mardiyana; Laila Fitriana (SOSIOEDUKASI, 2026)
This study aims to describe students’ creativity in STEAM learning through a pop-up book project based on the Engineering Design Process (EDP) in mathematics education, as viewed from the aspects of originality, flexibility, and elaboration. This study employs a descriptive qualitative approach. The research subjects consisted of three ninth-grade students selected using purposive sampling and grouped into high, medium, and low categories based on previous assessment results and analyzed in depth. Data were collected through observation, interviews, documentation, and product analysis. The research data were analyzed using the Miles and Huberman model, which includes data collection, data reduction, data presentation, as well as drawing conclusions and verification. The results of the study indicate that STEAM learning integrated with the EDP stages provides meaningful learning experiences through various activities and supports the development of students’ creativity. High-performing students demonstrated better abilities in originality, flexibility, and elaboration compared to students in other categories. Moderate-performing students showed fairly good creativity but still tended to adopt existing ideas or concepts. Meanwhile, low-performing students showed limitations in generating original ideas, adapting designs, and developing products in detail. The research findings indicate that the Ask and Imagine stages support idea exploration, the Plan and Create stages encourage design adjustments when facing obstacles, and the Improve stage provides students with the opportunity to reflect on and refine their pop-up books. Overall, the STEAM based pop-up book project supports the application of mathematical concepts through the creation of tangible products while fostering creativity through the integration of science, technology, engineering, art, and mathematics.